1985
DOI: 10.1159/000260840
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Demineralization and Maltose Clearance from Wheat Starch

Abstract: The ability of cooked starch (CS) and raw starch (RS)to cause intraoral enamel demineralization was determined by the iodide permeability (Ip) test which registers demineralization of enamel by an increase in Ip (+ΔIp) and mineralization by a decrease in Ip (––ΔIp). 5 subjects, who wore a palatal prosthesis holding 8 bovine enamel blocks covered by a layer of Streptococcus mutans swished 15 g of a 10% jelly of CS or 15 ml of a suspension of RS in the mouth for 1 min, and the change in Ip was determined after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
3
17
0
1
Order By: Relevance
“…Studies with this model have shown that raw and cooked wheat starch induced negligible and mild demineralization, respectively (Brudevold et al, 1985), whereas boiled gelatinized wheat starch gels (10, 15, or 20% starch) induced significant demineralization and significant pH drops (minimum pH of 4.8-5.0) (Brudevold et al, 1988). In the study by Kashket et a).…”
Section: Other Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies with this model have shown that raw and cooked wheat starch induced negligible and mild demineralization, respectively (Brudevold et al, 1985), whereas boiled gelatinized wheat starch gels (10, 15, or 20% starch) induced significant demineralization and significant pH drops (minimum pH of 4.8-5.0) (Brudevold et al, 1988). In the study by Kashket et a).…”
Section: Other Studiesmentioning
confidence: 97%
“…An intra-oral method has been developed that follows de-or remineralization of blocks of human enamel or dentin, or of bovine enamel, that are covered by a layer of S. mutans cells so as to mimic dental plaque (Brudevold et al, 1985;Kashket et al, 1994). Studies with this model have shown that raw and cooked wheat starch induced negligible and mild demineralization, respectively (Brudevold et al, 1985), whereas boiled gelatinized wheat starch gels (10, 15, or 20% starch) induced significant demineralization and significant pH drops (minimum pH of 4.8-5.0) (Brudevold et al, 1988).…”
Section: Other Studiesmentioning
confidence: 99%
“…This means plaque pH studies take no account of the protective factors found in some starch-containing food, nor do such studies account for the effect of foods on stimulation of salivary flow. Enamel slab experiments in humans have shown that raw starch does not cause demineralisation 126 and that cooked starch is about one-third to one-half as cariogenic as sucrose 127 . Animal studies have shown that raw starch is of low cariogenicity 128,129 ; cooked starch causes caries but only about half the amount caused by sucrose 130 .…”
Section: Starches and Dental Cariesmentioning
confidence: 99%
“…The ability of cooked starch and raw starch to cause enamel demineralization was also investigated using an intraoral demineralization test (Brudevold et al, 1985). This model involves the use of a palatal prosthesis holding bovine enamel slabs coated with a layer of S. mutans.…”
Section: Role Of A-amylase In Dental Cariesmentioning
confidence: 99%